EFEKTIVITAS MODEL PBL TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SDN 02 TANJUNG HARO KECAMATAN LUAK - Elsa Septa Wahyuni Elsa; Fetri Yeni J; Eldarni; Mutiara Felicita Amsal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this study is the conventional learning model that has been widely applied, resulting in students’ limited ability to analyze, evaluate, and solve science and social-based problems critically, as well as many students achieving scores below the Minimum Mastery Criteria (KKTP). This research aims to analyze the effectiveness of the Problem Based Learning (PBL) model on students’ critical thinking skills and learning outcomes in the subject of Science and Social Science Integration (IPAS) for fourth grade students at SDN 02 Tanjung Haro, Luak District. The research used a quantitative approach with an experimental method to compare students’ critical thinking skills and learning outcomes before and after the implementation of PBL. Data were collected through tests, observation sheets, and documentation, then analyzed statistically to determine the level of effectiveness. The results showed that the application of the PBL model significantly improved students’ critical thinking skills, as indicated by their ability to analyze and evaluate learning materials more effectively. In addition, student learning outcomes increased, with a higher number of students achieving scores above the KKTP compared to conventional learning methods. This study concludes that the PBL model is effective in improving both critical thinking skills and learning outcomes in IPAS subjects for elementary school students. The findings are expected to contribute to the development of innovative learning models in primary education and provide practical recommendations for teachers and schools to adopt PBL as an alternative strategy to enhance the quality of teaching and learning in rural contexts.